2000
DOI: 10.1002/(sici)1098-1136(20000201)29:3<233::aid-glia5>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Novel microtubule-associated protein-2 isoform is expressed early in human oligodendrocyte maturation

Abstract: We have identified a developmentally regulated, oligodendrocyte-specific protein, designated microtubule-associated protein-2 expressing exon 13 (MAP-2+13), in the human central nervous system (CNS). Monoclonal antibodies directed against MAP-2+13 labeled oligodendrocytes in the white matter of human fetal spinal cord. Double-label immunofluorescence and confocal microscopy, and immunoelectron microscopy localized MAP-2+13 to the soma and extending processes of fetal oligodendrocytes, but not to the myelin she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…To our knowledge, the only exceptions are MAP2c-expressing oligodendroglial progenitors occurring in multiple sclerosis plaques [48] or in HIV encephalitis [49]. In contrast to adult CNS in which MAP2a, MAP2b, and MAP2c are confined to neurons, glial precursor cells transiently express an alternatively spliced embryonic transcript including exon 13 (MAP2e) [33,36]. We uncovered a peculiar cell population offering a glial phenotype with a distinct expression of both the embryonic and the adult transcript of MAP2.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…To our knowledge, the only exceptions are MAP2c-expressing oligodendroglial progenitors occurring in multiple sclerosis plaques [48] or in HIV encephalitis [49]. In contrast to adult CNS in which MAP2a, MAP2b, and MAP2c are confined to neurons, glial precursor cells transiently express an alternatively spliced embryonic transcript including exon 13 (MAP2e) [33,36]. We uncovered a peculiar cell population offering a glial phenotype with a distinct expression of both the embryonic and the adult transcript of MAP2.…”
Section: Discussionsupporting
confidence: 87%
“…It binds to and stabilizes microtubules and is involved in cell proliferation as well as neuronal differentiation [28][29][30]. Each MAP2 transcript is the result of alternative splicing of a single gene located on human chromosome 2 [31][32][33]. The cellular expression of MAP2 and its splice forms are precisely regulated during brain development as well as in mature nervous tissue [28].…”
Section: Introductionmentioning
confidence: 56%
“…Studies have shown that MAP-2 expression was significantly increased during nerve injury, which represented reconstruction of dendritic structure to improve neurological function (Lin et al, 2015;Shafit-Zagardo et al, 2000;Uchida et al, 2015). MAP-2 is an important structural and functional protein found in the neuron bodies and dendrites for maintaining microtubule stability and nerve regeneration (Mohan and John, 2015).…”
Section: Discussionsupporting
confidence: 73%
“…Oligodendrocytes express several proteins in addition to tau that can contribute to oligodendrocyte microtubule assembly, stabilization, and organization during development. MAP1B and isoforms of MAP2 (Vouyiouklis and Brophy, 1993, 1995; Shafit‐Zagardo et al, 2000) are developmentally regulated in oligodendrocytes. Oligodendrocyte‐specific STOP (stable tubule‐only polypeptide) isoforms (Galiano et al, 2004) have been described, and microtubule interactions have been suggested for the myelin proteins 2′,3′‐cyclic nucleotide‐3′‐phosphodiesterase (CNP; Bifulco et al, 2002; Lee et al, 2005) and MBP (Galiano et al, 2006) as well as for qk1 (Zhao et al, 2006), stathmins (Liu et al, 2003; Southwood et al, 2004, 2007), and Fyn (Klein et al, 2002).…”
Section: Discussionmentioning
confidence: 99%